COUNTER-RADICALISM MOVEMENT AND HYBRIDIZATION OF IDENTITY IN THE YOUNG INTERFAITH COMMUNITY IN YOGYAKARTA (International Conference on Social and Islamic Studies, 2021)
The radicalism discourse that has been quite widespread in last two decades has produced various responses, ranging from counter-narrative, de-radicalization, and counter-radicalism efforts. This paper investigates specifically how efforts to counter radicalism are pursued from civil society initiatives, one of which is Young InterfaithPeacemaker Community (YIPC) in Yogyakarta. Using an interpretative phenomenological approach, this qualitative research explores several motives behind the counter radicalism movement that they organize and are equipped with avisible hybrid portraitof identity. Observation, informal interviews, and documentation are operated as dataretrieval techniques. The literature review was also deepened to elaborate data anddevelop argumentative narratives. The results obtained show that the three dialectical reasons that trigger them to counter radicalism are a collective awareness, imagined common enemy, and claims of youth fulness. In particular, the hybridization of identity that has been captured in this community can also be observed in changes in attitude,perspective, and behaviour patterns of individuals—before joining and when joining YIPC Yogyakarta. Borrowing from Gadamer’s concept, this was due to the mixture ofhorizons which later gave birth to a fused or assimilated character (hybrid) and reflected intheir speech, attitudes, social media content, and social actions.